Butyrate production from dietary fibre and protection against large bowel cancer in a rat model. - McIntyre, A (1993)
Butyrate slows the growth of cancer cells cultured in vitro. To determine the relevance of the fermentative production of butyrate in vivo, colonic butyrate concentrations were manipulated by feeding different dietary fibres and were related to tumour development in the rat dimethylhydrazine model of large bowel cancer. It has previously been shown that guar gum and oat bran, while highly fermentable, are associated with low butyrate levels in the distal colon, while wheat bran causes significantly higher concentrations. Diets containing these fibres (nominally 10% w:w) were administered for 3 weeks before, for 10 weeks during, and for 20 weeks after dimethylhydrazine administration, after which animals were killed and examined for tumours. Significantly fewer tumours were seen in the rats fed wheat bran compared with those fed guar or oat bran, and the total tumour mass was lowest in rats fed wheat bran. Rats on a 'no added fibre diet' had an intermediate tumour mass. Regression analysis, performed regardless of dietary group, showed that the concentration in stools of butyrate but not of acetate or stool volume, correlated significantly (and negatively) with tumour mass. These findings indicate that fibre which is associated with high butyrate concentrations in the distal large bowel is protective against large bowel cancer, while soluble fibres that do not raise distal butyrate concentrations, are not protective. Thus, butyrate production in vivo does bear a significant relationship to suppression of tumour formation.